IDENTIFYING GROWTH-DRIVING SECTORS IN YOGYAKARTA: A SECTORAL ANALYSIS FOR 2020–2023 - Asmara, Gea Dwi; Nurul Azizah Az Zakiyyah (Universitas Tidar, 2025)
This study aims to identify leading sectors with the potential to drive economic growth in the Special Region of Yogyakarta (DIY). It analyzes 17 economic sectors across all five districts in DIY during the period 2020–2023. The methods employed in this research include the Static Location Quotient (SLQ), Dynamic Location Quotient (DLQ), Growth Ratio Model (GRM), and Overlay Analysis. The results indicate that four economic sectors classified as leading sectors, namely Procurement of Water; Garbage Processing, Waste and Recycle; Information and Communication; Education Service; Health Service and Social Activity. These sectors are base sectors with strong prospects for continued development in the future and demonstrate high growth rates.